Learn Wireshark - Bock, Lisa (Birmingham : Packt Publishing, 2022)
"In this second edition of 'Learn Wireshark,' the author wants ti share her knowledge with the reader. Each chapter has multiple opportunities for a hands-o approach. Using the examples, the reader will make sense of the data and understand what the packets are telling you. This book is for network administrators, security analysts, students, teachers, and anyone interested in learning about packet analysis using Wireshark."
Includes index.
English.
Keywords: Computer networks